PENGARUH RETURN ON ASSET DAN CURRENT RATIO TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SUB SEKTOR TRANSPORT YANG TERDAFTAR DI BEI - Dona Elvia Desi; Rio Baviga (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to see the influence of Return On Assets and Current Ratio on Company Value with Company Size as a moderating variable in Transport Sub Sector Companies listed on the BEI for the 2013-2022 Period. By using a sample of 2 companies and the Moderated Regression Analysis (MRA) analysis tool, t test, F test and determinant coefficient, the result was that Return On Assets did not have a significant effect on Company Value (PBV) in Transport Sub Sector Companies Listed on the BEI for the 2013-2013 Period. 2022, with a t_count value of 0.282 < t_table of 2.101 while the Sig Return On Asset (X1) value is 0.781 > Sig 0.05, the Current Ratio has no significant effect on Company Value (PBV) in Transport Sub-Sector Companies Listed on the IDX for the 2013 Period -2022, with a t_count value of -0.695 > t_table of - 2.101 while the Sig Current Ratio (X2) value is 0.496 > Sig 0.05, Company Size does not moderate the influence of Return On Assets on Company Value (PBV) in Transport Sub Sector Companies Which Registered on the IDX for the 2013-2022 period, with a calculated t_value of 1.431< t_table of 2.145 while the Sig. 0.173 > from the Sig value. 0.05, Company Size does not moderate the influence of the Current Ratio on Company Value (PBV) in Transport Sub-Sector Companies Listed on the IDX for the 2013-2022 Period, with a calculated t_value of 1.564 < t_table of 2.145 while the Sig. 0.139 > Sig. 0.05 (alpha).